2009
DOI: 10.1182/blood-2008-05-159434
|View full text |Cite
|
Sign up to set email alerts
|

Role of activated protein C and its receptor in inhibition of tumor metastasis

Abstract: IntroductionMetastasizing cancer cells are thought to overcome the endothelial barrier through mechanisms commonly observed in leukocyte trafficking, including the up-regulation of adhesion molecules, apoptosis induction, cytoskeletal reorganization, and disruption of normal endothelial intercellular contacts. 1-5 Both cancer cell transmigration and leukocyte trafficking are increased by proinflammatory cytokines, such as interleukin-1␤ and tumor necrosis factor (TNF), which up-regulate adhesion molecules, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 26 publications
2
60
1
Order By: Relevance
“…In apparent contrast to our findings, in a model of melanoma, APC decreased lung metastasis by the ability to prevent tumor transmigration through the endothelial cells, by the EPCR/PAR1/ S1P1 axis (32,33). This difference is explained by the fact that the melanoma cell line did not expressed EPCR, and therefore APC effects were exclusively mediated by the EPCR expressed in endothelial cells.…”
Section: Mechanism Mediated By Epcr In Adccontrasting
confidence: 56%
“…In apparent contrast to our findings, in a model of melanoma, APC decreased lung metastasis by the ability to prevent tumor transmigration through the endothelial cells, by the EPCR/PAR1/ S1P1 axis (32,33). This difference is explained by the fact that the melanoma cell line did not expressed EPCR, and therefore APC effects were exclusively mediated by the EPCR expressed in endothelial cells.…”
Section: Mechanism Mediated By Epcr In Adccontrasting
confidence: 56%
“…We first examined the contribution of Dectin-2 to antitumor immunity by evaluating wild-type (WT) and Dectin-2-deficient (Dectin-2 KO) mice for subcutaneous tumor growth, lung metastasis, and liver metastasis of colon carcinoma cell line SL4, Lewis lung carcinoma cell line 3LL, and melanoma cell line B16F1 and B16F10, all of which have been demonstrated to undergo metastasis in mice (15)(16)(17)(18). We found that Dectin-2 KO mice showed more metastatic nodules in the liver compared with WT mice at 14 d after the intrasplenic inoculation with SL4, B16F1, or B16F10 cells, but not after inoculation with 3LL cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EPCR on the vascular wall inhibits cancer cell adhesion and transmigration (Bezuhly, 2009;Lindahl, 1993). Finally, significant resistance to APC was found in women with a lymph-node-positive breast carcinoma (Bezuhly, 2009;Lindahl, 1993;Nijziel, 2003). In a mouse model, endogenous APC has been found to limit cancer cell extravasation via sphingosine-1-phosphate receptor-1 and VE-cadherin-dependent vascular barrier enhancement.…”
Section: Cancermentioning
confidence: 98%
“…For example, EPCR is expressed on human breast cancer cells, with an extremely high frequency (Tsuneyoshi, 2001). EPCR on the vascular wall inhibits cancer cell adhesion and transmigration (Bezuhly, 2009;Lindahl, 1993). Finally, significant resistance to APC was found in women with a lymph-node-positive breast carcinoma (Bezuhly, 2009;Lindahl, 1993;Nijziel, 2003).…”
Section: Cancermentioning
confidence: 99%